Politics of Islamic Law in Indonesia During the Reformasi Era - Gafnel, Gafnel; Amin, Saiful; Fahmi, Khairul (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2024)
This study examines the politics of Islamic law in Indonesia during the Reformasi era, specifically during the administrations of Presidents B.J. Habibie, Abdurrahman Wahid (Gus Dur), and Megawati Soekarnoputri. This research employs a qualitative approach. The Reformasi era, which began after the fall of the Orde Baru regime in 1998, was marked by significant changes in Indonesia's legal and political systems. During Habibie's administration, political liberalization and efforts to strengthen the rule of law, including in the context of Islamic law, occurred. Gus Dur's era was characterized by more inclusive and pluralistic policies, as well as efforts to strengthen the position of Muslims in the national political and legal systems. Meanwhile, Megawati's administration focused on political and economic stability with a pragmatic approach to Islamic law. This study uses a descriptive-analytical method to understand the dynamics and shifts in Islamic law policies during these three administrations. The results indicate that the politics of Islamic law in Indonesia during the Reformasi era were significantly influenced by the political and social contexts of each administration, as well as the diverse aspirations of the Muslim community.